2009
DOI: 10.1002/jbm.a.32412
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of collagen in poly(3,4‐ethylenedioxythiophene) for a bifunctional film with high bio‐ and electrochemical activity

Abstract: Electrochemical polymerization can be used to directly synthesize conducting polymers while incorporating different functional molecules such as proteins for specific applications. There is a need to systematically study the effects of synthetic conditions for a polymer/protein composite on its nanostructure, chem/physical properties, and bioactivities. In this study, collagen, a cell-adhesion protein, was impregnated in poly(3,4-ethylenedioxythiophene) (PEDOT) via galvanostatic electropolymerization, and demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(30 citation statements)
references
References 29 publications
1
28
0
1
Order By: Relevance
“…15 PEDOT is an attractive polymer for the preparation of such biocomposites due to its excellent electrical stability, 3 high electrical conductivity, 16 and biocompatibility. 1719 Recent work has demonstrated that PEDOT is capable of incorporating large biomolecules including fibrinogen (MW = 330 kDa) 16 and collagen (MW = 300 kDa) 20 (Table 1). …”
Section: Introductionmentioning
confidence: 99%
“…15 PEDOT is an attractive polymer for the preparation of such biocomposites due to its excellent electrical stability, 3 high electrical conductivity, 16 and biocompatibility. 1719 Recent work has demonstrated that PEDOT is capable of incorporating large biomolecules including fibrinogen (MW = 330 kDa) 16 and collagen (MW = 300 kDa) 20 (Table 1). …”
Section: Introductionmentioning
confidence: 99%
“…Although the interaction between common CPs (i.e., polyaniline and, specially, polypyrrole derivatives) and bioentities, such as amino acids, proteins, DNA and living cells, has been extensively studied,8–16 it has been only quite recently that polythiophene derivatives have been explored as materials with promising biotechnological and/or biomedical applications 17–33. Within these exciting fields, PEDOT has been used to: recognize specific nucleotide sequences12–24; interact with epithelial, fibroblasts and neuronal cells favoring their adhesion and proliferation25–30; prepare bifunctional films with high bio‐ and electrochemical activities through the incorporation of collagen, which is one of the known constituents of the extracellular matrix of neurons31; construct functionalized devices for protein detection32, 33; etc.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous previous studies have revealed that conductive PEDOT can be polymerized by electrochemical polymerization of EDOT monomer and during this polymerization process, a variety of dopants can be incorporated into the PEDOT polymers [28,29]. In the present study, EDOT monomer, PSS, and chitosan were placed into the electrolyte solution and subjected to electrochemical polymerization.…”
Section: Discussionmentioning
confidence: 95%